2022
DOI: 10.1183/23120541.00540-2022
|View full text |Cite
|
Sign up to set email alerts
|

Airway clearance treatments in bronchiectasis: feasibility of linking survey results to registry data and a survey of patients’ and physiotherapists’ practices

Abstract: Background and objectiveThere are limited data on airway clearance treatment (ACT) practices. This study aimed (i) to assess the feasibility of collecting online surveys on ACTs from patients and physiotherapists and linking the patient survey data to outcome data in the Bronch-UK/EMBARC Registry; (ii) to assess the association between ACT practices and outcome data and (iii) to ascertain the factors affecting physiotherapist ACT practices.MethodsSurvey methodology was used to collect data from (i) patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Airway clearance techniques (ACTs) are central in the management strategy for patients with bronchiectasis (1). In our recent survey of 205 patients with bronchiectasis in Northern Ireland in the UK we described current practices for ACT in patients with bronchiectasis from the patient and physiotherapist perspective (2). We reported that physiotherapists are generally following the bronchiectasis guidelines and using the stepwise approach to management.…”
mentioning
confidence: 99%
“…Airway clearance techniques (ACTs) are central in the management strategy for patients with bronchiectasis (1). In our recent survey of 205 patients with bronchiectasis in Northern Ireland in the UK we described current practices for ACT in patients with bronchiectasis from the patient and physiotherapist perspective (2). We reported that physiotherapists are generally following the bronchiectasis guidelines and using the stepwise approach to management.…”
mentioning
confidence: 99%
“…In this issue of ERJ Open Research , M c L eese et al . [ 13 ] analysed the status quo of ACTs by performing online surveys among patients with bronchiectasis (consistent with the outcome data in the Bronch-UK/EMBARC Registry) and physiotherapists. The authors evaluated the feasibility of collecting ACT practice data online, the association between patient-reported ACT practice data and the outcomes in the Bronch-UK/EMBARC Registry, and the factors affecting physiotherapists’ decisions on initiating ACTs.…”
mentioning
confidence: 99%
“…A strength of the study design was that M c L eese et al . [ 13 ] quantified the dose of ACTs into three grades: low, medium and high dose. Patients performing ACTs (particularly high-dose ACTs) were more elderly and had more severe bronchiectasis (evidenced by the greater frequency of exacerbations in the previous year and lower quality of life).…”
mentioning
confidence: 99%
See 2 more Smart Citations